Gender-Specific Related Factors for Suicidal Ideation During COVID-19 Pandemic Lockdown Among 5,175 Chinese Adolescents - Zhu, Jin; Li, Baohua; Hao, Fengcheng; Luo, Linlin; Yue, Song; Zhai, Jinguo; Chen, Min; Liu, Yan; Liu, Debiao; Wang, JianLi (Frontiers in Public Health, 2022)
Background Suicide was an urgent issue during the pandemic period in adolescents. However, few studies were focused on suicide during the coronavirus disease 2019 (COVID-19) pandemic lockdown. Methods An online survey was conducted among 5,175 Chinese adolescents from June 9th to 29th in 2020 to investigate the prevalence of suicidal ideation (SI) during COVID-19 pandemic lockdown. A gender-specific stepwise logistic regression model was used. All analyses were performed with STATA 15.0. Results About 3% of the participants had reported having SI during the COVID-19 pandemic lockdown period. The prevalence of female SI (3.64%, 95% CI: 2.97–4.45%) was higher than that of males (2.39%, 95% CI: 1.88–3.05%) (χ2 = 6.87, p = 0.009). Quarreling with parents [odds ratio (OR) = 9.73, 95% CI: 5.38–17.59], insomnia (OR = 5.28, 95% CI: 2.81–9.93), previous suicide attempt history (OR = 3.68, 95% CI: 1.69–8.03), previous SI history (OR = 2.81, 95% CI: 1.30–6.06), and feeling depressed during pandemic lockdown (OR = 2.26, 95% CI: 1.22–4.18) were positively associated with the males' SI. However, having emptiness inside (OR = 4.39, 95% CI: 2.19–8.79), quarreling with parents (OR = 3.72, 95% CI: 2.16–6.41), insomnia (OR = 3.28, 95% CI: 1.85–5.80), feeling anxious (OR = 2.62, 95% CI: 1.46–4.70), and longing for father's emotional warmth (OR = 0.38, 0.20–0.72) were associated mostly with females' SI. Conclusions Female adolescents, who felt emptiness from their families and their fathers' emotional warmth, were at much higher risk of having SI during COVID-19 lockdown. We must specify a suicide prevention policy and interventions for adolescents in the pandemic crisis based on gender gaps.